The practice of hospice care in a patient with end-stage gastrointestinal stromal tumor (1例胃肠道间质瘤终末期患者的安宁疗护实践) - MENG Xiangnan (孟祥楠); CAO Hongjing (曹红京) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the clinical experience of hospice care in a patient with end-stage gastrointestinal stromal tumor. The concept, knowledge and skills of hospice care were used to nurse a patient with gastrointestinal stromal tumor in the terminal stage, to help the patient to control symptoms, to provide comfortable care, to solve physical problems and to provide psychological support, spiritual care was provided through dignity therapy and meaning therapy; the patient's right to decision-making was respected, and pre-medical care plans were discussed and family members were instructed to participate effectively in the care. (本文总结1例胃肠道间质瘤终末期患者安宁疗护的临床经验。 运用安宁疗护的理念、知识和技能, 对1例胃肠道间质瘤终末期患者进行护理, 帮助患者症状控制, 提供舒适照护, 解决躯体问题, 提供心理支持; 评估灵性需求, 采取尊严疗法和意义疗法, 提供灵性照护; 尊重患者的自主决策权, 谈论预先医疗照护计划, 指导家属有效参与护理。)